Predicting the Tendency towards Rhinoplasty Based on Obsessive-Compulsive Personality Disorder and Body image - Tajally, Romina; Mechi, Farahnaz; khoshsirat, shahrokh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: The prevalence of mental disorders and injuries among cosmetic surgery applicants is higher than normal people. Aim: The aim of the present study was to predict the tendency towards rhinoplasty based on obsessive compulsive personality disorder and body image. Methods: The study population consisted of 100 people (30 males and 70 females) applicants for rhinoplasty who were selected by convenience sampling method by referring to three limited surgery clinics in Tehran. The instruments included the Millon Clinical Multiaxial Inventory-III (MCMI-III) and the Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBSRQ). Data analysis was performed using Pearson correlation test and multiple regressions in SPSS ver.21. Results: The findings showed a significant positive relationship between obsessive compulsive personality disorder and body image, AE subscale, AO subscale, and BAS subscale with tendency towards rhinoplasty. Also, the results of regression analysis showed that obsessive compulsive personality disorder (16.3% (R2 = 0.163)) and body image (14% (R2 = 0.141)) and altogether explain 54% (R2 = 0.540) of the tendency towards rhinoplasty. Conclusion: Most people who refer to cosmetic surgery clinics have obsessive-compulsive tendencies and negative body image, and, therefore, it is recommended that clients undergo psychological evaluation in these clinics before surgery.